OPTIMALISASI PELAYANAN PUBLIK MELALUI PEMANFAATAN TEKNOLOGI INFORMASI DI DESA TIMORENG PANUA KABUPATEN SIDENRENG RAPPANG - haeruddin, haeruddin; Ikbal, Muhammad (JOURNAL OF GOVERNMENT (Kajian Manajemen Pemerintahan dan Otonomi Daerah), 2019)
This study aims to know the optimization of services through the use of information and communication technology in the Timoreng Panua village Pancarijang district Sidenreng Rappang district, in terms of the eight types of data the research approach used in this study is a qualitative approach. The type of research approach is descriptive, descriptive research is research that seeks to tell the solution of existing problems based on data. Data analysis techniques used in this study use the following techniques: data reduction data collection, data display, verification and conclusion conclusionsThe services carried out in Timoreng Panua Village are still with a manual system because various things faced include inaccurate data so that officials still make improvements to population data as found on the website. family card data even though the data of the whole community in Timoreng Panua has been inputted on the village website so that while the website-based service has not been fully implemented until it has been made to improve population data.